Eksistensi Alquran Pusaka dalam Perkembangan Mushaf - Zaenal Abidin (JOURNAL OF QUR'AN AND HADITH STUDIES, 2019)
This article seeks the existance of Quran Pusaka, first official Indonesian Quran in 1960. The seeking refer to mushaf studies that develop till today. In addition to library data (specially Pusaka Quranic manuscript), this article uses interview data then explained by discriptive-analytic. This article argues that Quran Pusaka did not become a reference for published Quran, although Abu Bakar Aceh regarded it as Mushaf Imam. Furthemore, this Quran is lacked of attention by government and  Nusantara Quranic scholars. The evidence are, Bayt Al-Quran and Istiqlal Museum wrote a wrong leaflet, and Quran Pusaka was not mentioned in  the history of Indonesian Quranic Standard book.